Mentor Teachers' Perceptions Toward the Pedagogical Competence of Pre-Service Teacher Professional Education, FKIP, University of Palangka Raya in Practical Field Experience - Pinardi, Janu; Rahman, Abdul; Basuki, Bejo; Artuti, Emy; Ratnawati, Oktaviana Ainun (JURNAL PENDIDIKAN, 2024)
This study aimed to determine student teachers' perceptions about the mastery of pedagogical competencies of students of the PPG Pre-service Study Program at FKIP Palangka Raya University in 2022 in Field Experience Practice. This research uses a quantitative approach with a descriptive research type. The research involved 15 student teachers as subjects, with the object being 62 students of the Pre-service PPG Study Program at FKIP Palangka Raya University in 2022, namely wave I as many as 33 people, and wave II as many as 29 people. Data collection was carried out using a questionnaire that had been validated by three experts and obtained a value of V (Aiken Index) = 0.92> 0.8 including in the high category and a PA value (Percentage of agreement) = 93%, meaning that it was feasible to use to collect data. The results showed that in wave I, 3 students (9.09%) were obtained in the high category, 24 students (72.73%) in the medium category and 6 students (18.18%) in the low category, and wave II, 4 students (13.79%) were obtained in the high category, 20 students (68.97%) in the medium category and 5 students (17.24%) in the low category. From waves I and II, it can be seen that the largest frequency is in the medium category, so it can be concluded that the perceptions of student teachers about the mastery of pedagogical competence of students of the PPG Study Program at FKIP Palangka Raya University in 2022 are in the medium category.